Effect of Oriented Electric Fields on Biologically Relevant Iron–Sulfur Clusters and Bioinformatics Investigations of Biotin Synthase - Gaughan, Samuel J H (2023)
Enzymes, as biological catalysts, enjoy several benefits over the more commonly used metal catalysts in chemistry, particularly in terms of sustainability. They can, however, be more complicated to utilise and manipulate and research tends to focus on engineering enzymes for specific tasks where the complexity is reduced and a by-product of this is increased understanding of sequence-structure-function relationship. An alternative approach is to find broader problems whose solutions could be applied to the engineering of many enzymes, or at least a large, multipurpose superfamily of them. An excellent target for this type of approach is the radical S-adenosylmethionine (rSAM) superfamily, particularly due to its common mechanism of generating a radical species and using careful substrate control to dictate the reaction products across the different enzymes. This common mechanism includes an iron-sulfur cluster which can be influenced by the electrostatic environment, providing a clear path for study and promising powerful engineering opportunities. The focus of this research is an analysis of the effect of oriented electric fields on several relevant iron-sulfur clusters using a systematic, high throughput density-functional theory (DFT) study to gain both quantitative and qualitative information on the relative energies of spin states, orbitals, vertical electron affinities and spin-coupling constants. In addition, methods are identified for coupling this type of study with bioinformatic information for the purpose of enzyme engineering. Applying this to an exemplar of the rSAM superfamily, biotin synthase (BioB), indicates promising scope for variation at iron-sulfur cluster binding sites, whilst retaining functionality. Both the DFT results and the bioinformatics analysis represent a promising step towards the potential automation of enzyme engineering and is not limited to biotin synthase or even rSAM enzymes. This could result in improved development of a wide variety of chemical products in sustainable, efficient, and low-carbon syntheses, with the concomitant contributions to mitigating climate change.